Haptic teleoperation systems signal processing perspective - Lee, Jae-young (Springer International Publishing, 2015)
This book examines the signal processing perspective in haptic teleoperation systems. This text covers the topics of prediction, estimation, architecture, data compression, and error correction that can be applied to haptic teleoperation systems. The authors begin with an overview of haptic teleoperation systems, then look at a Bayesian approach to haptic teleoperation systems. They move onto a discussion of haptic data compression, haptic data digitization and forward error correction. · Presents haptic data prediction/estimation methods that compensate for unreliable networks · Discusses haptic data compression that reduces haptic data size over limited network bandwidth and haptic data error correction that compensate for packet loss problem · Provides signal processing techniques used with existing control architecture